Evolution of Seed Dispersal Modes in the Orchidaceae: Has the Vanilla Mystery Been Solved? - Karremans Lok, Adam Philip (2023)
Orchid seeds are predominantly wind-dispersed, often developed within dry, dehiscent fruits that typically release millions of dust-like seeds into the air. Animal-mediated seed dispersal is a lesser-known phenomenon in the family and predominantly occurs in groups belonging to early-diverging lineages bearing indehiscent, fleshy fruits with hard, rounded, dark seeds. In this review, we explore the evolutionary trends of seed dispersal mechanisms in Orchidaceae, focusing on the pantropical genus Vanilla. Notably, certain Neotropical species of Vanilla produce vanillin- aromatic compounds synthesized naturally in their fruits, which plays a pivotal role in seed dispersal. Ectozoochory occurs in dry, dehiscent fruits, whose seeds are dispersed by (i) male euglossine bees collecting the fruit’s vanillin aromatic compounds and (ii) female stingless bees collecting the fruit’s mesocarp. Endozoochory occurs in (iii) highly nutritious, indehiscent fruits consumed by terrestrial mammals or (iv) fleshy, dehiscent fruits whose mesocarp is consumed by arboreal mammals. Wind dispersal appears to be a derived state in Orchidaceae and, given its predominance, a trait likely associated with enhanced speciation rates. Zoochory primarily occurs in groups derived from early- diverging lineages; occasional reversions suggest a link between dispersal mode and fruit and seed traits. Interestingly, fruit dehiscence and fleshiness in Vanilla lack phylogenetic signal despite their role in determining dispersal modes, suggesting potential environmental adaptability.